Impact on Inflammation and Recovery of Skin Barrier by Nordihydroguaiaretic Acid as a Protease-Activated Receptor 2 Antagonist - Kim, Hyo Young (The Korean Society of Applied Pharmacology, 2012)
Atopic dermatitis is a chronic, inflammatory disease of the skin with increased transepidermal water loss. Both an abnormal inflammatory response and a defective skin barrier are known to be involved in the pathogenesis of atopic dermatitis. Protease activated receptor 2 (PAR2) belongs to a family of G-protein coupled receptors and is activated by both trypsin and a specific agonist peptide, SLIGKV-NH(2). PAR2 is expressed in suprabasal layers of the epidermis and regulates inflammatory responses and barrier homeostasis. In this study, we show that nordihydroguaiaretic acid (NDGA) inhibits the PAR2-mediated signal pathway and plays a role in skin barrier recovery in atopic dermatitis. Specifically, NDGA reduces the mobilization of intracellular Ca(2+) in HaCaT keratinocytes by down-regulating inflammatory mediators, such as interleukin-8, thymus and activation-regulated chemokine and intercellular cell adhesion molecule-1 in HaCaT keratinocytes. Also, NDGA decreases the protein expression of involucrin, a differentiation maker of keratinocyte, in both HaCaT keratinocytes and normal human epidermal keratinocytes. We examined NDGA-recovered skin barrier in atopic dermatitis by using an oxazolone-induced atopic dermatitis model in hairless mice. Topical application of NDGA produced an increase in transepidermal water loss recovery and a decrease in serum IgE level, without weight loss. Accordingly, we suggest that NDGA acts as a PAR2 antagonist and may be a possible therapeutic agent for atopic dermatitis.